Discretion of Public Order Agency (Satpol PP) in Enforcing Regional Regulations: A Normative Review of Conditions, Limits and Accountability - Nasar, Muhammad; Bhakti, Rizki Tri Anugrah; Maileni, Dwi Afni; Sakti, Indra (Dinasti Research, 2026)
This study aims to formulate the legal basis for the Public Order Agency (Satpol PP) discretion in enforcing regional regulations, focusing on the distinction between routine and discretionary authority, the conditions for exercising discretion, normative limits, and the legal accountability model. The study uses a normative juridical method with a statutory and conceptual approach. Primary, secondary, and tertiary legal materials are analyzed through legal interpretation, systematic reasoning, and legal argumentation to develop operational parameters for testing discretion in the practice of enforcing regional regulations. The results show that the main problem does not lie in the existence of discretion, but rather in the absence of consistent parameters for assessing the validity, limits, and accountability of its use. The study produced six main findings, namely the classification of Satpol PP actions between routine and discretionary authority; formal and material conditions for the use of discretion; a matrix for testing the limits of discretion based on legality, general principles of good governance (AUPB), the purpose of authority and proportionality; a typology of risks of deviation; a legal accountability model; and the operational flow of discretion as a framework for institutional evaluation. The findings confirm that the Public Order Agency (Satpol PP)discretion remains legitimate within the framework of a state governed by law, provided it is based on clear authority, a documented rationale, appropriate position objectives, and verifiable accountability mechanisms. This research contributes to strengthening regional administrative law and improving governance to achieve more measurable and accountable regional regulatory enforcement. More specifically, the primary novelty of this study lies in the formulation of an operational flow of Satpol PP discretion that translates abstract principles of legality, AUPB, purpose of authority, proportionality, documentation, and correction into a sequential decision-making framework that can be applied institutionally in daily regional regulation enforcement.